THE STUDY ON THE LEVEL OF SATISFACTION OF LOCAL COMMUNITY TOWARDS THE INFRASTRUCTURE DEVELOPMENT IN AYER LANAS - Noor Farahin Kamarul Baharin (2013)
Development is one of the important key in identifying the ability of any country in fulfilling the demand of economic as well as social. One of the development aspect that being highlighted is the development of infrastructure. The level of effectiveness and the quality of the infrastructure development that had been done will relatively giving impact to the social and economic system of the area. Thus, this research is focus on the spatial database of infrastructure development in Ayer Lanas, Jeli. The purpose of this study is to identify the distribution of infrastructure in Ayer Lanas and the level of satisfaction of the local people towards the infrastructure that had been provided. The result is divided into two part which are geographical data and social data. In geographical data, GIS software is used in producing map of distribution of infrastructure in Ayer Lanas while the social data is obtained from the questionnaire that had been distributed to the local people. The results show that the local people are satisfied with the infrastructure that had been provided. In the other hand, more infrastructure development need to be carry out as the number of population are increasing. This is also important as Ayer Lanas will be developed to be one of the main trading area for the district of Jeli. Any development activities that will be carry out are believed to give significance impact to the local people.